1999
DOI: 10.1182/blood.v94.6.1878
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB–Dependent Induction of Interleukin-8 Gene Expression by Tumor Necrosis Factor : Evidence for an Antioxidant Sensitive Activating Pathway Distinct From Nuclear Translocation

Abstract: Tumor necrosis factor  (TNF) is a pluripotent activator of inflammation by inducing a proinflammatory cytokine cascade. This phenomenon is mediated, in part, through inducible expression of the CXC chemokine, interleukin-8 (IL-8). In this study, we investigate the role of TNF-inducible reactive oxygen species (ROS) in IL-8 expression by “monocyte-like” U937 histiocytic lymphoma cells. TNF is a rapid activator of IL-8 gene expression by U937, producing a 50-fold induction of mRNA within 1 hour of treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(96 citation statements)
references
References 44 publications
3
92
0
1
Order By: Relevance
“…It is well-established that calpain and proteasome pathways mediate cytoplasmic proteolysis of IκB inhibitors to release NFκB from cytoplasmic stores [26], resulting in exposure of nuclear localization sequences promoting efficient translocation of NFκB into the nucleus. However, we made the seminal observation that nuclear translocation alone is insufficient to activate innate NFκB-dependent networks [27,28]. The mechanism underlying viral induced NFκB activation is via the production of reactive oxygen species (ROS)-induced nuclear damage.…”
Section: The Airway Epithelial Cell As a Sensor Of Rsv Replicationmentioning
confidence: 99%
“…It is well-established that calpain and proteasome pathways mediate cytoplasmic proteolysis of IκB inhibitors to release NFκB from cytoplasmic stores [26], resulting in exposure of nuclear localization sequences promoting efficient translocation of NFκB into the nucleus. However, we made the seminal observation that nuclear translocation alone is insufficient to activate innate NFκB-dependent networks [27,28]. The mechanism underlying viral induced NFκB activation is via the production of reactive oxygen species (ROS)-induced nuclear damage.…”
Section: The Airway Epithelial Cell As a Sensor Of Rsv Replicationmentioning
confidence: 99%
“…Tumour necrosis factor‐ α (TNF‐ α ) is a major factor in the development of chronic inflammatory conditions (Maini & Taylor, 2000). This cytokine elicits a wide spectrum of cellular responses including leukocyte adhesion and migration as well as activation of inflammatory cells, with enhanced secretion of additional mediators such as interleukin‐1 and interleukin‐8 (Vassalli, 1992; Vlahopoulos et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We found that IFN‐β was increasingly expressed 1 day after infection and kept increasing in the time observed and was thought to have immune adjuvant effect in corneal infection. TNF‐α has been proved to be a kind of apoptosis‐inducing cytokines and may play the same role in this process, which resulted in the tissue (34).…”
Section: Discussionmentioning
confidence: 99%